CONTRIBUTION OF CHOIR CONDUCTORS TERĒZE BROKA AND STANISLAVS BROKS TO THE DEVELOPMENT OF LATGALIAN CULTURE IN DAUGAVPILS IN THE 60s OF THE 20TH CENTURY - Rancāne, Anna (Via Latgalica, 2017)
Latgalian culture of the 60s and 70s of the 20th century is still insufficiently studied and evaluated. Although this time in Latvia is marked by the dominance of the Soviet ideology in all spheres of social life, russification, and ban of Latgalian print, there were people who managed to develop Latgalian identity and culture. Terēze Broka (1925) and Stanislavs Broks (1926–1977), the two outstanding choir conductors, are among such people. After graduation from Latvia State Conservatory they were appointed to work in Daugavpils. In this city, characterized by Russian spirit and with no choirs, the two conductors within a short period of time managed to establish musical collectives and develop repertoires where along with the obligatory Soviet songs Latgalian folk songs were included. In autumn 1954, Terēze Broka established a women’s vocal ensemble „Daina” and a group of kokle (a Latvian national musical instrument) players, and looked for more unknown Latgalian songs at the Academy of Sciences of the Latvian SSR. The folk songs were arranged by her husband, conductor and director of Daugavpils Music College Stanislavs Broks who in 1956 established a mixed choir, later called „Daugava”. Due to their persevering work in a short period of time both Daugavpils musical collectives gained brilliant success and were nominated to the VI World Youth and Students Festival in Moscow in summer 1957 where they were awarded the silver prize. This success is followed by the bright parade of Latgalian performance, the week of Latgalian culture in Riga in December 1958, where the two Daugavpils collectives were at the centre of all events. It is noteworthy that the two collectives mainly consisted of Latvians, Russians and Poles who did not know the Latgalian language, but were diligent and motivated to learn to be able to sing in Broks’ collectives. In 1961 the Latvian Music Department in Minneapolis (USA) released the first disc of the Latgalian folk songs “Latgalian (Latvian) Folk songs“ compiled by Mikelis Bukšs. The disc contains 15 music pieces from the repertoire of Daugavpils mixed choir „Daugava” (conducted by S. Broks) and the women’s vocal ensemble „Daina” (led by T. Broka). „Aiz azara bolti bārzi”, „Aiz azara augsti kolni...”, „Siermi zyrgi, jauni puiši...”, „Audzit muni gari lyni”, „Es sovai māmeņai...” and other Latgalian folk songs arrangements served as a specific brand of Daugavpils, which strengthened the self-confidence of Latgalians of that time.